2021
DOI: 10.26508/lsa.202101049
|View full text |Cite
|
Sign up to set email alerts
|

Incomplete antiviral treatment may induce longer durations of viral shedding during SARS-CoV-2 infection

Abstract: The duration of viral shedding is determined by a balance between de novo infection and removal of infected cells. That is, if infection is completely blocked with antiviral drugs (100% inhibition), the duration of viral shedding is minimal and is determined by the length of virus production. However, some mathematical models predict that if infected individuals are treated with antiviral drugs with efficacy below 100%, viral shedding may last longer than without treatment because further de novo infections ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 54 publications
2
12
0
2
Order By: Relevance
“…We show that suboptimal exposure to the simulated antiviral inside simulated infected epithelial tissues leads to regrowth of viral load between doses and may contribute to persistent COVID-19. This result aligns with the reported experiments in non-human primate, rhesus macaques [15][16][17].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We show that suboptimal exposure to the simulated antiviral inside simulated infected epithelial tissues leads to regrowth of viral load between doses and may contribute to persistent COVID-19. This result aligns with the reported experiments in non-human primate, rhesus macaques [15][16][17].…”
Section: Discussionsupporting
confidence: 93%
“…There are several antiviral drugs with similar MOAs [ 11 , 12 ], and previous modeling works simulated treatment with these drugs [ 13 , 14 ]. Experiments on SARS-CoV-2 infection in non-human primates (rhesus macaques) and associated mathematical models have shown that an antiviral drug treatment with lower efficacy may elongate the duration of the viremic profile even if the treatment initiation is very early [ 15 , 16 , 17 ]. Given these results, the present model focuses on the relations of the drug potency, treatment initiation time and dose interval with the viraemia as crucial players, and performs a thorough scan of all related parameters to elucidate a reasonable treatment regimen.…”
Section: Introductionmentioning
confidence: 99%
“…Fourth, we did not include the cases received antiviral therapy because of lack of information about its effect for SARS-CoV-2. However, once enough data about those antivirals are available, we can include those cases (we have already proposed a model accounting for antiviral effect [ 38 , 65 , 66 ]).…”
Section: Discussionmentioning
confidence: 99%
“…Several mathematical models have been developed detailing SARS-CoV-2 viral kinetics in humans (Cao et al, 2021;Goyal et al, 2020;Ke et al, 2021aKe et al, , 2021bKim et al, 2021a;Ne ´ant et al, 2021), nonhuman primates (Dobrovolny, 2020;Gonc ¸alves et al, 2021;Kim et al, 2021b;Rodriguez and Dobrovolny, 2021), and ferrets (Vaidya et al, 2021). The general structure follows a target cell-limited model with or without innate and adaptive immune responses.…”
Section: Introductionmentioning
confidence: 99%
“…The general structure follows a target cell-limited model with or without innate and adaptive immune responses. In particular to modeling in nonhuman primates, Dobrovolny (2020) and Kim et al (2021b) explained the observed prolonged viral shedding in nasal passages with early treatment with remdesivir. However, these studies did not provide an explanation for viral kinetics in the lung under treatment along with observed improved pathogenesis in treated animals.…”
Section: Introductionmentioning
confidence: 99%